2021
DOI: 10.1111/bjep.12442
|View full text |Cite
|
Sign up to set email alerts
|

Shaping classroom social experiences through collaborative small‐group discussions

Abstract: Background. Students form interpersonal and intrapersonal classroom social experiences with peers. While diverse intervention programmes have been developed, few have integrated social-emotional learning into academic activities to maximize the potential for learning and development.Aims. This study examined the effects of collaborative small-group discussions on students' classroom social experiences at the interpersonal and intrapersonal levels.Sample. The study included 250 students (M age = 10.98, female =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Nonetheless, if teachers successfully balance the cognitive and social dimensions of group dialogues, they not only support the development of students' social reasoning, but also their interpersonal negotiation strategies, which transfer to children's social life in the classroom. Accordingly, Lin et al (2021) showed that compared with children in the control group (read-aloud and regular instruction), children participating in the CSR group were accepted more by peers and showed less peernominated aggressive behavior.…”
Section: Educational Approachesmentioning
confidence: 98%
See 1 more Smart Citation
“…Nonetheless, if teachers successfully balance the cognitive and social dimensions of group dialogues, they not only support the development of students' social reasoning, but also their interpersonal negotiation strategies, which transfer to children's social life in the classroom. Accordingly, Lin et al (2021) showed that compared with children in the control group (read-aloud and regular instruction), children participating in the CSR group were accepted more by peers and showed less peernominated aggressive behavior.…”
Section: Educational Approachesmentioning
confidence: 98%
“…Collaborative Social Reasoning (CSR) (Lin et al, 2019(Lin et al, , 2021) is a six-week literary program that includes six to ten discussions about narrative fictional texts. The texts address provocative questions about friendships, social exclusion, ethics of care, and responsibility that should invite controversial discussions around a "big question."…”
Section: Educational Approachesmentioning
confidence: 99%
“…Collaborative Social Reasoning (Lin et al, 2019, 2022) is a peer-centered small group dialogic approach informed by the literature on Collaborative Reasoning (Chinn et al, 2001; Reznitskaya et al, 2009). The CSR approach provides an ideal context to examine the links between collaborative dialogue and individuals’ SPT as an internalized ability because it has been found to promote individuals’ positive social experiences and social reasoning (Lin et al, 2019, 2022), both of which are positive correlates of SPT development (Batanova & Loukas, 2011; Kim et al, 2023; Smith & Rose, 2011). The design of CSR involves three theoretical and research-driven features aimed at creating collaborative, reciprocal, and supportive social contexts to facilitate SPT.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Each student's ability to learn and interact with educators is influenced by their personality, family backgrounds, mental processes, learning styles, priorities, maturity levels, and academic ambitions (Tucker, 2021). Social constructivist theories suggest that learning is effective when students feel they are part of a community of positively interacting peers who learn from and with each other (Lin et al, 2021). Discussion with peers is critical to student learning and improves comprehension and engagement in various settings (Cazden, 2001).…”
Section: Top Hatmentioning
confidence: 99%
“…Discussion with peers is critical to student learning and improves comprehension and engagement in various settings (Cazden, 2001). Through peer discussion in the classroom, students have the opportunity to jointly use their interpersonal and intrapersonal thinking skills to improve collective and individual learning (Lin et al, 2021). Effective classroom discussion provides important opportunities for students to practice social and emotional skills, including communicating effectively and disagreeing respectfully.…”
Section: Top Hatmentioning
confidence: 99%